Academic goals and learning strategies of pre-service teachers during emergency online learning in the Philippines - Acebes, Swen Joshryll; Malitante, Jaizel; Tuble, Nikki; Bongolto, Rowena (CV Rezki Media, 2025)
Background: The COVID-19 pandemic has lasted an extended period, during which many students have reported being adversely affected by the escalating global crisis. Objectives: This study examined the academic goals, learning barriers, facilitative strategies, and ways forward of pre-service teachers during emergency online learning. Methods: This qualitative case study employed content analysis to examine data gathered through focus group discussions. To explore the implications of survey findings and gain deeper insights into students' perspectives on remote learning, the researchers conducted Focus Group Discussions (FGDs) with twelve purposively selected pre-service teachers via Google Meet. The discussion transcripts were analyzed to construct a compelling narrative, supported by literature and prior research, to explain emerging themes. Results: Among the twelve participants, ten reported experiencing psychosocial stress, eight cited recurring technical issues, and seven mentioned financial constraints as significant learning barriers. Despite these challenges, the participants remained motivated to complete their coursework, viewing academic achievement as a stepping stone toward improving their socio-economic conditions. They employed various strategies, including scheduling, note-taking, goal-setting, optimistic thinking, parental scaffolding, and systematic planning, to adapt to online learning. To ensure credibility, the researchers used member checking, peer debriefing, and FGD and survey data triangulation. Conclusions: These findings highlight the resilience and adaptability of pre-service teachers in navigating the challenges of emergency online learning, underscoring the need for supportive institutional policies and resources. Future research may consider comparing student experiences in public and private institutions or examining the long-term impact of emergency remote learning on teaching efficacy. Pedagogical and academic implications are further discussed.